Performing Below the Targeted Level: An Investigation into KS3 Pupils’ Attitudes Towards Mathematics - Anusha Mirza; Nasreen Hussain (Journal of Education and Educational Development, 2020)
This study sets out to investigate the attitude KS3 pupils have towards mathematics and the factors that influence this attitude. A case study approach was used as the pupils were a unit of the school under study and a survey method was chosen to provide scope to the study.  Purposeful sampling was employed for the selection of 200 pupils from years 7 and 9 who were from target achiever and non target achiever groups.  Attitudes Toward Mathematics Inventory (Tapia, 1996) was administered to the participants to measure their attitude towards mathematics. Data were analysed using Statistical Package for the Social Sciences (SPSS) version 17.  The result for the first hypothesis indicated that there is a significant difference on the variable of mathematics attitude of year 7 and 9 target achievers and non target achievers pupils (t=4.11, df =199, p
Keywords: mathematics attitudes; secondary level; target achievers; under achievers